Pemberian Campuran Nutrisi AB Mix dengan Limbah Cair Kelapa Sawit Sebagai Pupuk pada Tanaman Sawi Hijau (Brassica chinensis var. Parachinensis) dengan Metode Hidrponik - Zuleika, Divia Laila; Triyono, Sugeng; Tusi, Ahmad; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2024)
Palm oil mill effluent (POME), discharged by palm oil processing industry, is potentially recovered as substitution of AB mix, a nutrient solution for hydroponic. The objective of this research is to test the use of the treated POME in the mixture with AB mix to cultivate green mustard. The method in this study uses a factorial Completely Randomized Design (CRD) with 2 factors.  The first factor, namely POME (K) consists of 2 levels, namely Pond 3 (K3) and Pond 4 (K4).  The second factor is the mixture of AB Mix and POME, which consists of 5 levels of the POME percentages namely: 0% (P0), 25% (P25), 50% (P50), 75% (P75), and 100% (P100). Results showed that the increasing percentages of POME additions tended to decrease the growth of green mustard. The best treatment was obtained on treatment of P0, 100% AB mix with no POME addition based on plant height, number of leaves, and water consumption. Keywords: AB Mix, Green Mustard, Hydroponic, POME, Wick System